Using human rights to counter terrorism - Nowak, Manfred; Charbord, Anne (Elgar studies in human rights, 2018)
Key trends in the fight against terrorism and key aspects of international human rights law / Manfred Nowak and Anne Charbord -- Impact of post 9/11 counter-terrorism measures on all human rights / Martin Scheinin -- New counter-terrorism measures : Continuing challenges for human rights / Ben Emmerson -- The complexity and challenges of addressing the conditions conducive to terrorism / Fionnuala Ní Aoláin -- One step forward, two steps back : The Security Council, 'foreign terrorist fighters', and human rights / Lisa Ginsborg -- Acting ethically in the shadows : intelligence gathering and human rights / Richard Barrett and Tom Parker -- The preventive criminal justice strategy against terrorism and its human rights implications / Ulrich Garms -- Questions of accountability in countering terrorism / Lisa Oldring